H2O2 and Ca2+ Signaling Crosstalk Counteracts ABA to Induce Seed Germination - Mengjie Cheng; Yanliang Guo; Qing Liu; Sanwa Nan; Yuxing Xue; Chunhua Wei; Yong Zhang; Feishi Luan; Xian Zhang; Hao Li (MDPI AG, 2022)
Seed germination is a critical stage and the first step in the plant's life cycle. H2O2 and Ca2+ act as important signal molecules in regulating plant growth and development and in providing defense against numerous stresses; however, their crosstalk in modulating seed germination remains largely unaddressed. In the current study, we report that H2O2 and Ca2+ counteracted abscisic acid (ABA) to induce seed germination in melon and Arabidopsis by modulating ABA and gibberellic acid (GA3) balance. H2O2 treatment induced a Ca2+ influx in melon seeds accompanied by the upregulation of cyclic nucleotide-gated ion channel(CNGC) 20, which encodes a plasma membrane Ca2+-permeable channel. However, the inhibition of cytoplasmic free Ca2+ elevation in the melon seeds and Arabidopsis mutant atcngc20 compromised H2O2-induced germination under ABA stress. CaCl2 induced H2O2 accumulation accompanied by the upregulation of respiratory burst oxidase homologue(RBOH) D and RBOHF in melon seeds with ABA pretreatment. However, inhibition of H2O2 accumulation in the melon seeds and Arabidopsis mutant atrbohd and atrbohf abolished CaCl2-induced germination under ABA stress. The current study reveals a novel mechanism in which H2O2 and Ca2+ signaling crosstalk offsets ABA to induce seed germination. H2O2 induces Ca2+ influx, which in turn increases H2O2 accumulation, thus forming a reciprocal positive-regulatory loop to maintain a balance between ABA and GA3 and promote seed germination under ABA stress.